Isolation and molecular characterization of Lumpy skin disease virus fromcattle and the detection of anti-viral antibodies in buffaloes - YADAV, SARITA; BOORA, ASHOK; DEVI, PARVINA; NISHU; VERMA, NISHA; SINGH, INDERJEET; KUMAR, ANIL (The Indian Journal of Animal Sciences, 2024)
In the present study, four LSDV field strains were isolated from cattle in Bhadra tehsil, Hanumangarh district, Rajasthan under ICAR-Farmer FIRST Project and Bathinda, Punjab during the period 2021 and 2022. Apart from the characteristic clinical signs of LSD, the viral etiology was confirmed by PCR targeting LSDV074, LSDV 117 and LSDV036 genes, in addition to characteristic clinical signs LSD in cattle. Though, buffalo is a susceptible host, only mild deep seated skin nodules suspected for LSD were reported from in-contact buffaloes under field condition in this study. None of the samples from buffalo were found positive for LSDV, BHV-1 and BHV-2 DNA by PCR. Buffaloes exhibiting mild clinical signs in the current study showed an antibody titre of 1:16 to 1:64 by virus neutralization assay. No information is available regarding the seroprevalence of LSD in buffalo from India, therefore, it is imperative to further investigate the susceptibility of buffalo to LSDV infection. Based on the phylogenetic analysis of the ORF036 gene sequence, LSDV/India/RAJ/ OP604055/2021 was in close relationship with LSDV from India, Kenya, Nepal, Bangladesh and Myanmar as they clustered together as a sub-cluster.